Influence of biliary cirrhosis on the detoxification and elimination of a food derived carcinogen. Issue 12 (11th November 2004) - Dietrich, C G; Geier, A; Wasmuth, H E; Matern, S; Gartung, C; de Waart, D R; Elferink, R P J O
Abstract : Background and aims: The liver is the central organ for the detoxification of numerous xenobiotics, including carcinogens. We studied the influence of cholestasis and biliary cirrhosis on the detoxification, elimination, and tissue distribution of a model compound and food derived carcinogen, 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP). Methods: Wistar rats were injected with 14 C-PhIP into the portal vein one or six weeks after common bile duct ligation (CBDL). Bile flow was reconstituted, bile and urine were collected over 120 minutes, and metabolites were analysed using high performance liquid chromatograpy. Total tissue radioactivity levels in several organs as well as tissue bound (ethanol insoluble tissue fraction) radioactivity levels were determined. Results: Significant downregulation of the transport proteins multidrug resistance associated protein 2 and breast cancer resistance protein was observed in biliary cirrhosis. Biliary excretion of radioactivity was significantly reduced in cholestasis and biliary cirrhosis compared with controls (15 (2.9)% and 3.2 (1)% of the dose v 36.5 (2)%, respectively). Phase II metabolism was severely reduced in cirrhotic rats, resulting in a twofold increase in tissue radioactivity levels in the liver, kidney, and colon. Biliary cirrhosis increased tissue binding of reactive metabolites, as expressed in cpm/100 mg tissue in the liver and the colon (3267 (1218) v 1191 (429) in the liver, 3044 (1913) v 453 (253) in the colon). Conclusions: Biliary cirrhosis induced by CBDL causes impaired metabolism and elimination of PhIP, and leads to higher tissue levels of potentially genotoxic metabolites in the liver and colon of rats. These data may explain the increased incidence of hepatic and extrahepatic cancers in cholestasis and liver cirrhosis.